Exploring the Effect of the Pace Model on Students’ Grammar Mastery and Students’ Voices on Its Usage - Asfi Aniuranti; M.Happy Nur Tsani; Yasinta Wulandari (Faculty of Language and Literature, University of Surakarta, 2022)
Students commonly regard grammar as a challenging element of English. Therefore, every English teacher is always encouraged to use effective alternatives. Furthermore, the teaching and learning process that is still running online often causes many obstacles. One of the recommended teaching models for grammar class is PACE Model. This study explored the effectiveness of the PACE model to teach English grammar and students’ voices toward this model. The method employed was pre-experimental research or one group pre-test post-test design. For collecting the data, the team employed a test and a questionnaire. The data were analysed using simple statistical calculations like average and percentage. The result revealed that the PACE model is an effective way of teaching English grammar because the average score of the post-test (52.33) was higher than the pre-test (24.67). There was a significant improvement in the test result. The data from the questionnaire also showed that most of the students had positive perceptions about the usage of the PACE Model. Overall, the PACE model was an adequate model to teach English grammar online because it received positive responses from the students